Projection Mapping Demo (iCREATE Open Day 2024) - Auzani Zeda, Mohamed Kassim
On October 19, 2024, the Institute of Creative Arts and Technology hosted a Research Open Day at the Borneo Cultures Museum. One of the key highlights of the event was a live projection mapping demonstration. The session introduced the audience to the fascinating world of projection mapping, showcasing its creative possibilities and technical processes. Using MadMapper software, the demonstration provided a hands-on overview of how visuals can be mapped onto surfaces to create immersive and dynamic experiences. This activity aimed to inspire attendees by highlighting the intersection of art and technology.